PERBANDINGAN MEKANISME PERUBAHAN UNDANG-UNDANG DASAR ANTARA INDONESIA DENGAN AMERIKA SERIKAT - Marzuk, Farid Arista; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Every country had a constitution that become a ground rules for another rules that come after it.constitution was a rules about constitutional or polity thing, that in Indonesia, we actually call it Undang-Undang Dasar (UUD). Every constitution always load some changing clause in its text, because considering about how unperfectly human works including make that constitution thing. United State of America and Indonesia was two country that adopt presidential government system within republic form. And furthermore, government institution that had a authority to change the constitution of each country was a legislature. In United State of America, the institution that can change the constitution was called Congress which include House of Representative and Senate, and in Indonesia, the institution that can change the constitution was called Majelis Permusyawaratan Rakyat (MPR) which include Dewan Perwakilan Rakyat (DPR) and Dewan Perwakilan Daerah (DPD) within. And when we talk about the step how to changing clause made, it has own rules within.Keywords: constitution, amendment of the constitution, United State of America, Indonesia